Effects of water absorption on Napier grass fibre/polyester composites. (1st June 2016) - Haameem J.A., M.; Abdul Majid, M.S.; Afendi, M.; Marzuki, H.F.A.; Hilmi, E. Ahmad; Fahmi, I.; Gibson, A.G.
Abstract: The effect of moisture absorption on untreated and alkaline-treated Napier grass fibre-reinforced polyester composites was evaluated. Under room-temperature immersion, the water absorption behaviour of the Napier grass fibre composites conformed to the Fickian diffusion mechanism. Compared with the untreated fibres, the treated fibres absorbed less water due to the removal of lignin and hemicelluloses. The tensile and flexural strength of the Napier grass composites decreased with increased water absorption. SEM analysis showed that the treated Napier grass fibre composites contained fewer fibre pull-outs and splits compared with the untreated composites, which supports the improved performance.